Strategi Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatera Utara dalam Peningkatan Mutu Perguruan Tinggi Swasta - Nasution, Efrida Yanti; Sailah, Illah; Hermadi, Irman (Jurnal Penjaminan Mutu, 2021)
This study aims to analyze internal and external factors and formulate strategies in improving the quality of higher education institutions in LLDIKTI Region I, North Sumatra. This research uses descriptive quantitative research methods. The analysis method used is a SWOT analysis using an analysis of internal factors and external factors. Strategies that can be carried out by LLDIKTI Region I North Sumatra are improvement and development of data-based information systems in coaching the quality of private universities, internal strengthening of LLDIKTI Region I North Sumatra in terms of more competent human resources, implementing and developing data-based decision support systems that can map quality PTS, guidance in implementing SPMI, provides training to increase the number of qualified auditors.